Efficiency of Light Outcoupling Structures in Organic Light‐Emitting Diodes: 2D TiO2 Array as a Model System. (25th March 2019) - Will, Paul‐Anton; Schmidt, Maximilian; Eckhardt, Kai; Wisser, Florian; Lenk, Simone; Grothe, Julia; Kaskel, Stefan; Reineke, Sebastian
Abstract: Organic light‐emitting diodes (OLEDs) are widely used in research and are established in the industry. The building block nature of organic compounds enables a vast variety of materials. On top of that, there exist many strategies to improve the light outcoupling of OLEDs making a direct comparison of outcoupling technologies difficult. Here, a novel approach is introduced for the evaluation of light outcoupling structures. The new defined "efficiency of light outcoupling structures" (ELOS) clearly determines the effectiveness of the light outcoupling structure by weighting the experimental efficiency enhancement over the theoretical outcoupling gain. It neither depends on cavity design nor on the chosen organic material. The methodology is illustrated for red phosphorescent OLEDs comprising internal and external light outcoupling structures. Assumptions and further uses are discussed with respect to experimental and theoretical handling. In addition, the ELOS is calculated for various outcoupling techniques from literature to demonstrate the universality. Finally, most suitable reference OLEDs are discussed for application of light outcoupling structures. The presented approach enables new possibilities for studying light outcoupling structures and improves their comparability in a highly material‐driven research field. Abstract : A novel evaluation method of light outcoupling structures for organic light‐emitting diodes is presented. Compared to established efficiencies, i.e., external quantum and light outcoupling efficiency, the so‐called "efficiency of light outcoupling structures" assesses only the light outcoupling technology by weighting experimental enhancement over potential gain. Assumptions, usage, and a brief rating of light outcoupling techniques from literature are discussed.